Agile approach for developing financial management application in pharmacies - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to develop financial management applications in pharmacies with the Extreme Programming (XP) approach to overcome the complexity and diversity of financial processes and the demands of a rapidly changing market and intense competition in the pharmaceutical industry. The research method consists of three stages: data collection, application development, and user acceptance evaluation. Data collection was conducted through interviews and a literature review. Application development used XP principles to enable flexibility and adaptability in responding to changing user needs. User acceptance evaluation was conducted to identify the advantages and disadvantages of the application as well as the level of user satisfaction. The results showed that the developed application successfully fulfilled most user needs, with the user satisfaction level reaching 85%. This research contributes to providing an effective solution for managing dispensary financial processes with the XP approach and a better understanding of user needs and expectations in the rapidly growing pharmaceutical industry.